The Impact of Natural Disasters on Secondary School Enrollment Rates - Kaur, Harpaljit; Shah Habibullah, Muzafar; Nagaratnam, Shalini (International Journal of Engineering and Technology, 2018)
This paper examines the impact of total disasters and four individual natural disasters (flood, storm, drought and earthquake) on secondary school enrollment rates using panel data over the period 1970 to 2014. For robustness check, we use four measures on each of these natural disasters; the number of occurrence, number of death, number of people affected and the estimatedÂ damages caused by natural disasters as a percentage of GDP;Â thus we employ twenty natural disaster variables. In addition, we re-estimate all specification using lag of natural disaster variables to capture the delayed effect of these variables on enrollment. Employing the system Generalized Method of Moment (GMM) model, the findings show that the number of occurrences and disaster related losses (death, affected and damages) significantly contribute to the rates of secondary school enrollment. The current study also found that the secondary school enrollment rates are more affected by the contemporaneous effects of natural disaster for the exception of total disasters and floods, which are affected by both the medium and long-term effects. One unanticipated finding that emerge from the analysis is that earthquake have a positive effect on secondary enrollment rates in the long-term.Â Â